OVERVIEW OF THE IMPLEMENTATION OF DIGITAL TRANSFORMATION IN PAYMENT SERVICES IN THE HOSPITALITY (British Journal of Global Ecology and Sustainable Development, 2024)
Digital transformation in the hotel industry, which adopted a digital payment system with a responsive approach to the global payment market, has created a significant opportunity to improve operational efficiency and customer satisfaction as a means of implementing an integrated digital payment system that can improve transaction speed and security. Digital payment technology offers customers flexibility by providing a variety of payment options. The purpose of this study is to understand the positive and negative effects that the hotel industry experiences. This study employs the positive and negative dampening factors of digital transformation, namely, Positive effects include: (1) Increasing operational efficiency; (2) Raising service quality; (3) Raising data security; (4) Raising payment processing efficiency; and (5) Raising warehouse productivity. Drawbacks: (1) Dependency on technology; (2) Difficulty in developing applications; (3) Difficulty in maintaining digital security.